Tax shields in Colombia and their effect on leverage and investments (2014)
The is article studies the determin ing factors of leverage and investment for Colombian companies between 1995 and 2009. Regarding leverage we test ed the predictions of the t rade - o ff and p ecking o rder t heories, particularly the impact of tax incentives and interest rates. We f ou nd that leverage decreased after enacting the tax incentive of 2003 and tha t interest rate s increase leverage. We d id not find any strong evidence of greater investment as a result of tax incentives.